Behavioral Considerations in Management Accounting Theory and Practice - Musov, Michael (Research Papers, 2022)
The paper explores the question of what the future of behavioral accounting research in management accounting is. It contributes to the Bulgarian accounting theory by highlighting behavioral problems as an important research area for the future development of management accounting. More generally the paper contributes to the existing literature with the deductive justification of behavioral considerations being an integral and fundamental part of the theory and practice of management accounting. The first and second sections examine the early behavioral problems of the Anglo-Saxon practice and theory of accounting in general and management accounting in particular. The third section describes various behavioral issues discussed in Bulgarian accounting literature. The last section argues that the impact of the management accounting function – its contribution to the development and implementation of the strategy – depends heavily on the influence of management accounting information on the subjective mental representations of its primary users.